Critical review of soil contamination by polybrominated diphenyl ethers (PBDEs) and novel brominated flame retardants (NBFRs); concentrations, sources and congener profiles - Thomas McGrath; Andrew Ball; Bradley Clarke (2017)
Polybrominated diphenyl ethers (PBDEs) have been used in a broad array of polymeric materials such as plastics, foams, resins and adhesives to inhibit the spread of fires since the 1970s. The widespread environmental contamination and well documented toxic effects of PBDEs have led to bans and voluntary withdrawals in many jurisdictions. Replacement novel brominated flame retardants (NBFRs) have, however, exhibited many of the same toxic characteristics as PBDEs and appear to share similar environmental fate. This paper presents a critical review of the scientific literature regarding PBDE and NBFR contamination of surface soils internationally, with the secondary objective of identifying probable pollution sources. An evaluation of NBFR distribution in soil was also conducted to assess the suitability of the newer compounds as replacements for PBDEs, with respect to their land contamination potential. Principle production of PBDEs and NBFRs and their consequent use in secondary polymer manufacture appear to be processes with strong potential to contaminate surrounding soils. Evidence suggests that PBDEs and NBFRs are also released from flame retarded products during disposal via landfill, dumping, incineration and recycling. While the land application of sewage sludge represents another major pathway of soil contamination it is not considered in this review as it is extensively covered elsewhere. Both PBDEs and NBFRs were commonly detected at background locations including Antarctica and northern polar regions. PBDE congener profiles in soil were broadly representative of the major constituents in Penta-, Octa- and Deca-BDE commercial mixtures and related to predicted market place demand. BDE-209 dominated soil profiles, followed by BDE-99 and BDE-47. Although further research is required to gain baseline data on NBFRs in soil, the current state of scientific literature suggests that NBFRs pose a similar risk to land contamination as PBDEs.